Oxidative depolymerization of lignosulfonates to low-molecular weight aromatics: an interlaboratory study - Norberg, Mynta; Bekirovska, Selda ; 0009-0000-4519-2091; Klein, Jana; Moeller, Finn; Gustafson, Karl P. J.; Sandahl, Margareta; Hulteberg, Christian P. ; 0000-0002-3502-5529; Turner, Charlotta ; 0000-0001-9466-1149; Abdelaziz, Omar Y.; Waldvogel, Siegfried R.; Spégel, Peter; Bengtsson, Oskar (RSC Sustainability, 2025)
In the pursuit of sustainable chemical production, feedstock diversification is essential. Lignosulfonates, a water-soluble aromatic byproduct of the sulfite pulping process, offer a green alternative for producing value-added compounds such as vanillin via oxidative depolymerization. However, current depolymerization processes are not comparable due to inconsistencies in feedstocks and a lack of validated analytical methods. In the present study, we developed and validated a novel sample preparation and GC/FID method for quantifying vanillin, vanillic acid, and acetovanillone. Three oxidation processes—continuous alkaline (CA), heterogeneous metal-catalysed (HMC), and electrochemical nickel anode (ENA)—were optimized and compared using the same feedstock. A round-robin test ensured analytical comparability across different labs. The analytical method demonstrated high precision (<5% intra-lab, <10% inter-day, and <25% inter-lab RSD) for all compounds. The HMC oxidation process yielded the highest total monomer concentration (4.3 g L−1) and monomer yield (8.7 wt%), while CA oxidation achieved the highest volumetric productivity (up to 840 g (L × h)−1). Future work should explore hybrid approaches leveraging the strengths of these oxidative lignin depolymerisation processes.